PENGARUH RASIO KEUANGAN DAN REPUTASI UNDERWRITER TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2005-2008 - Neneng Sri Suprihatin (Universitas Serang Raya, 2016)
The purpose of this study is to determine the effect of financial ratio and underwriter reputation. The independent variable are financial ratio and underwriter reputation. The dependent variable is financial distress.The sample used in the study consists of manufacturing companies listed and delisted the period of 2005-2008. The result show are financial ratio and underwriter reputation no influence on financial distress positive whether or partial simultaneouslyKeyword :financial ratio, underwriter reputation, and financial distress.